Advanced electrolyte/additive for lithium-ion batteries with silicon anode. (August 2016) - Zhang, Shuo; He, Meinan; Su, Chi-Cheung; Zhang, Zhengcheng
Highlights: Recent progress in new electrolytes for silicon anode was reviewed. Recent development in functional electrolyte additives for silicon anode was reviewed. Mechanistic studies on electrolyte/additive decomposition were demonstrated. Future research prospects were envisioned. Abstract : State-of-the-art lithium-ion batteries (LIBs) are based on a lithium transition metal oxide cathode, a graphite anode and a nonaqueous carbonate electrolyte. To further increase the energy and power density of LIBs, silicon anodes have been intensively explored due to their high theoretical capacity, low operation potential, and low cost. However, the main challenges for Si anode are the large volume change during lithiation/delithiation process and the instability of the solid-electrolyte-interphase associated with this process. Recently, significant progress has been achieved via advanced material fabrication technologies and rational electrolyte design in terms of improving the Coulombic efficiency and capacity retention. In this paper, new developments in advanced electrolyte and additive for LIBs with Si anode were systematically reviewed, and perspectives over future research were suggested.